2021
DOI: 10.1093/qjmed/hcab029
|View full text |Cite
|
Sign up to set email alerts
|

Should COVID-19 Patients > 75 Years be Ventilated? An Outcome Study

Abstract: Background Elderly patients with COVID-19 disease are at increased risk for adverse outcomes. Current data regarding disease characteristics and outcomes in this population is limited. Aim To delineate the adverse factors associated with outcomes of COVID- 19 patients ≥75 years of age. Design Retrospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We also found that patients presented after about a week of symptom onset (mean 6.7 days) as reported in Table 1. Studies with other racial groups have also consistently shown that older age is associated with worse outcomes [9,10,11]. Increasing susceptibility to Covid-19 disease with age can be attributed to the immunosenescence of the aging immune system [12].…”
Section: Discussionmentioning
confidence: 95%
“…We also found that patients presented after about a week of symptom onset (mean 6.7 days) as reported in Table 1. Studies with other racial groups have also consistently shown that older age is associated with worse outcomes [9,10,11]. Increasing susceptibility to Covid-19 disease with age can be attributed to the immunosenescence of the aging immune system [12].…”
Section: Discussionmentioning
confidence: 95%
“…Dementia has also been reported as an independent risk factor for mortality. [20] Since it is di cult to obtain informed consent from patients with dementia, the focus shifts to the patient's family members or relatives who can provide proxy consent for IMV. However, as mentioned above, it is di cult to have a discussion with the patient's family members and relatives in the acute phase of COVID-19.…”
Section: Discussionmentioning
confidence: 99%